The Validity of Single Candidates in Regional Head Elections - Chusnul Khitam, Muhammad; Faizah, Niswatun; Shodiq, Ja’far; Khuluq, Muhammad Husnul (Jurnal Independent, 2026)
Democracy is a system where the people as the holders of the highest power have the right in all decision-making that includes the interests of the people in a region. In this case, indirectly the people can also issue laws and regulations that are beneficial and also to protect their rights. The 1945 Constitution of the Republic of Indonesia, Article 1 paragraph (2) of the 1945 Constitution which reads "sovereignty is in the hands of the people and is implemented according to the Constitution". This study aims to answer two main problem formulations. First, What is the role of the Election Supervisory Body in supervising the nomination of regional heads? Second, What is the validity of a single candidate in the regional election from a democratic perspective? This study uses the Normative Juridical research method. While the approach used is the Legislation approach (statue approach). The results of the study show: First, Bawaslu has a role in supervising the nomination of regional heads, namely: Supervising registration, Verifying candidates, Preventing violations, Handling violations, Monitoring campaigns. Second, the validity of a single candidate in the regional elections from a democratic perspective, namely regulated in Article 54C and 54D of Law Number 10 of 2016 concerning the second amendment to Law Number 1 of 2015 concerning the stipulation of the Replacement of Law Number 1 of 2014 concerning the election of Governors, Regents, and Mayors.